Bankruptcy Analysis With Altman, Springate, And Zmijewski On Consumer Goods Companies Listed On The Indonesian Stock Exchange - Julianto Julianto; Zulkifli Zulkifli; Agustinus Miranda (Jurnal Stagflasi : Ekonomi, Manajemen dan Akuntansi, 2023)
Financial statement analysis is very important for companies that go public, these financial reports become company performance reports for investors, suppliers, and employees because they are the most disadvantaged if the company loses money or goes bankrupt. The analysis needs to be done, with the consideration that the bankruptcy of a go public company will harm many parties. The object of this study is a consumer goods company listed on the Indonesia Stock Exchange (IDX) and included in the IDX30 indexed company class, the data used to analyze company bankruptcy using financial statement data for the 2016-2021 period. The purpose of this study is to determine the financial performance and devastation in the last five consecutive years. The method of analysis in this study is the analysis of financial statement ratios and bankruptcy analysis of the Altman Z-Score model, the Springate model and the Zmijewski model.